Idiopathic Spinal Cord Herniation—Case Report - Sacco, Rogerio Cirineo; Gepp, Ricardo de Amoreira; Quiroga, Marco Rolando Sainz; Souza, Henrique Caetano de; Aguiar, Vitor Viana Bonan de; Santos, Romel Corecha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Idiopathic spinal cord herniation is a rare cause of progressive myelopathy, especially in the absence of a history of spinal or surgical trauma. The radiological diagnosis is made through a myelography or an MRI exam. The spinal cord is pushed anteriorly, buffering the dural defect and leading in most cases to Brown-Séquard syndrome. The present study describes the case of a male patient with a clinical picture of progressive thoracic myelopathy. In the clinical and radiological investigation, an idiopathic spinal cord herniation on the chest level was identified. During the surgery, the spinal cord was reduced to the natural site, taking its usual elliptical shape, and the dural defect was repaired with a dural substitute. The numbness of the patient improved, and the shocks in the lower limbs disappeared. A postoperative MRI confirmed the surgical reduction of the herniation and the restoration of the anterior cerebrospinal fluid (CSF) column to the spinal cord. The authors describe the clinical, radiological, intraoperative, and postoperative evolution.
Keywords: spinal cord diseases; Brown-Séquard syndrome; myelography; magnetic resonance imaging; hernia; surgery